Quantitative characterization of the aqueous fraction from hydrothermal liquefaction of algae. (October 2016) - Maddi, Balakrishna; Panisko, Ellen; Wietsma, Thomas; Lemmon, Teresa; Swita, Marie; Albrecht, Karl; Howe, Daniel
Abstract: The aqueous fraction generated from hydrothermal liquefaction (HTL) of algae contains approximately 20–35% of the total carbon present in the algal feed. Hence, this aqueous fraction can be utilized to produce liquid fuels and/or specialty chemicals for economic sustainability of HTL on an industrial scale. In this study, aqueous fractions produced from HTL of freshwater and saline-water algal cultures were analyzed using a wide variety of analytical instruments to determine their compositional characteristics. Organic chemical compounds present in eight aqueous fractions were identified using two-dimensional gas chromatography equipped with time-of-flight mass spectrometry. Identified compounds include organic acids, nitrogen compounds and aldehydes/ketones. Conventional gas chromatography and liquid chromatography methods were utilized to quantify the identified compounds. Inorganic species in the aqueous stream from HTL of algae also were quantified using ion chromatography and inductively coupled plasma optical emission spectroscopy. The concentrations of organic chemical compounds and inorganic species are reported. The amount quantified carbon ranged from 45 to 72% of the total carbon in the aqueous fractions. Highlights: The total carbon yield in the aqueous fraction from hydrothermal liquefaction of algae was 20–35 wt%. 45–72% of the total carbon in the aqueous fraction was identified and quantified. 41–85% of the total nitrogen in the aqueous fraction was identified and quantified. Organic species were mainly organic acids, alcohols, ketones and nitrogenous compounds. Inorganic species included chloride salts of Ca, K, Mg and Na.